2015
DOI: 10.1039/c5cy00118h
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene formation by methane dehydrogenation and C–C coupling reaction on a stoichiometric IrO2 (110) surface – a density functional theory investigation

Abstract: The capability to activate methane at mild temperature and facilitate all elementary reactions on the catalyst surface is a defining characteristic of an efficient catalyst especially for the direct conversion of methane to ethylene. In this work, theoretical calculations are performed to explore such catalytic characteristic of an IrO 2 (110) surface. The energetics and mechanism for methane dehydrogenation reactions, as well as C-C coupling reactions on the IrO 2 (110) surface, are investigated by using van … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 66 publications
2
46
0
Order By: Relevance
“…18,19 Such an interaction between the C−H bond and the metal atom is also known as an agostic interaction. 20 Jiang et al have theoretically proposed a mechanism for activating methane on the IrO 2 (110) surface and converting it to ethylene 21 as well as a mechanism for promoting the generation of formaldehyde from methane by applying electric field on the same catalyst surface. 22 Cao and co-workers have performed a machine-learning study using surface-structure descriptors to predict the reaction mechanism of methane activation on oxide surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Such an interaction between the C−H bond and the metal atom is also known as an agostic interaction. 20 Jiang et al have theoretically proposed a mechanism for activating methane on the IrO 2 (110) surface and converting it to ethylene 21 as well as a mechanism for promoting the generation of formaldehyde from methane by applying electric field on the same catalyst surface. 22 Cao and co-workers have performed a machine-learning study using surface-structure descriptors to predict the reaction mechanism of methane activation on oxide surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The next step in the CH 4 oxidation is CH 4 binding. According to some recent reports,, long range interaction plays an important role in the interaction between CH 4 and catalysts. By using the long‐range corrected CAM−B3LYP functional, we find that there is an attraction between CH 4 and O(4) of the [Cu 3 (μ‐O) 2 (7‐ N ‐Etppz)] 1+ complex to form a C−H(1)⋅⋅⋅O(4) hydrogen‐bond with a distance of 2.151 Å (Figures ( a ) and ( b )).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the development of catalysts to activate the C−H bonds in CH 4 has received considerable interest over the years. In recent studies, selective CH 4 oxidation has been investigated by using various catalysts, including the methane monooxygenases (MMOs), pure metal catalysts, metal oxide systems, as well as Cu‐based and Fe‐based zeolites. MMOs, which convert CH 4 to CH 3 OH at nearly room temperatures and normal pressure by using O 2 as the oxidant, have been demonstrated to be the most efficient CH 4 oxidizers .…”
Section: Introductionmentioning
confidence: 99%
“…The B and N‐co‐doped graphene can be synthesized experimentally at different concentrations, although the synthesis of B‐doped graphene or N‐doped graphene is challenging; in addition, the application of B and N to tune up the band gap of graphene at the Fermi level is difficult . Furthermore, previous studies have demonstrated that methane can be molecularly adsorbed on the IrO 2 (110) surface and supported Ir clusters through agostic interactions . These agostic interactions help to weaken the metal coordinated C‐H bonds, which, in turn, help to lower the barrier of the C─H bond cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…To maintain the sustainability of energy and environment, finding an alternative energy source is one of the key issues of late. In this regard, methane is currently receiving attention from petrochemical industries due to its abundance and to the advancement of shale gas extraction technology for the conversion of methane to value‐added products . Methane conversion is a major area of interest in the field of catalytic science and technology owing to the abundance of methane and the possibility of efficiently converting it to value‐added products through indirect and one‐step (direct process) processes.…”
Section: Introductionmentioning
confidence: 99%